1997
DOI: 10.1084/jem.185.10.1793
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Epitope on the Entamoeba histolytica 170-kD Lectin Conferring Antibody-mediated Protection against Invasive Amebiasis

Abstract: The emergence of multidrug-resistant organisms and the failure to eradicate infection by a number of important pathogens has led to increased efforts to develop vaccines to prevent infectious diseases. However, the nature of the immune response to vaccination with a given antigen can be complex and unpredictable. An example is the galactose– and N-acetylgalactosamine–inhibitable lectin, a surface antigen of Entamoeba histolytica that has been identified as a major candidate in a vaccine to prevent amebiasis. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 24 publications
3
58
2
Order By: Relevance
“…The humoral response may account for the protection observed in the animals inoculated with the mixture of the plasmids. In fact, studies using both active and passive immunization strategies suggest that certain antibodies to E. histolytica may protect against liver abscesses (Lotter et al, 1997;Seydel et al, 1996;Zhang et al, 1994). The cellular response did not augment in the protected animals, although with these experiments we cannot discard differences in the quality of the cellular response with the different immunization protocols.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The humoral response may account for the protection observed in the animals inoculated with the mixture of the plasmids. In fact, studies using both active and passive immunization strategies suggest that certain antibodies to E. histolytica may protect against liver abscesses (Lotter et al, 1997;Seydel et al, 1996;Zhang et al, 1994). The cellular response did not augment in the protected animals, although with these experiments we cannot discard differences in the quality of the cellular response with the different immunization protocols.…”
Section: Discussionmentioning
confidence: 77%
“…It has been reported that DNA vaccines promote the cellular response more than the humoral one (Kowalczyk & Ertl, 1999), and experimental evidence suggests that the cellular response has a predominant role in protection against amoebiasis (Campbell & Chadee, 1997;Schain et al, 1995), although the role of the humoral response has also been documented (Lotter et al, 1997;Seydel et al, 1996;Zhang et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in the levels of protection were statistically significant only with Yersinia cells transformed either with YopE-T-170CP or YopE-T-170CR2 (Table 1). The protective potential of 170CR2 to inhibit amebic liver abscess in gerbils has been shown previously (9,10). However, the potential of 170CP to induce protective immunity is surprising, as previous studies have shown that high titers of serum immunoglobulin G anti- bodies to this fragment exacerbate amebic disease (10).…”
mentioning
confidence: 91%
“…The protective potential of 170CR2 to inhibit amebic liver abscess in gerbils has been shown previously (9,10). However, the potential of 170CP to induce protective immunity is surprising, as previous studies have shown that high titers of serum immunoglobulin G anti- bodies to this fragment exacerbate amebic disease (10). Interestingly, analysis of antibody responses after oral infection with recombinant Yersinia cells indicated that the observed protection was most likely mediated by antibody-independent immune mechanisms, as antibody titers were relatively low compared to those from previous intraperitoneal vaccination trials with recombinant ameba lectin (10) and there was no correlation between the degree of protection and titers of antibodies (Fig.…”
mentioning
confidence: 99%
“…In vitro diagnostic tests have been developed to discriminate infection by pathogenic amoebae from infection by non-pathogenic amoebae. A possible candidate antigen for a vaccine has been identified (Lotter et al 1997).…”
Section: Specific Research Programsmentioning
confidence: 99%